2019
DOI: 10.18632/aging.102355
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin for longevity: opinion article

Abstract: From the dawn of civilization, humanity has dreamed of immortality. So why didn’t the discovery of the anti-aging properties of mTOR inhibitors change the world forever? I will discuss several reasons, including fear of the actual and fictional side effects of rapamycin, everolimus and other clinically-approved drugs, arguing that no real side effects preclude their use as anti-aging drugs today. Furthermore, the alternative to the reversible (and avoidable) side effects of rapamycin/everolimus are the irrever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(91 citation statements)
references
References 202 publications
(191 reference statements)
2
89
0
Order By: Relevance
“…Rapamycin, an allosteric inhibitor of mechanistic target of rapamycin (mTOR), prolongs life in yeast, worms, flies, and mice. Rapamycin also prevents age-related conditions in rodents, dogs, nonhuman primates, and humans (Blagosklonny, 2019). mTOR is a critical nutrient sensor and has multiple downstream effects, including protein synthesis, and autophagy.…”
Section: The Role Of Mitophagy In Agingmentioning
confidence: 99%
“…Rapamycin, an allosteric inhibitor of mechanistic target of rapamycin (mTOR), prolongs life in yeast, worms, flies, and mice. Rapamycin also prevents age-related conditions in rodents, dogs, nonhuman primates, and humans (Blagosklonny, 2019). mTOR is a critical nutrient sensor and has multiple downstream effects, including protein synthesis, and autophagy.…”
Section: The Role Of Mitophagy In Agingmentioning
confidence: 99%
“…Therefore, when it was observed that rapamycin increased the longevity of mice, there were questions about the translatability of using rapamycin to delay aging in humans because of its potential negative effect on the immune system. However, it is now recognized that rapamycin is best identified as an immunomodulator rather than an immunosuppressant [44,87]. Because of its use in transplant patients and its potential anti-aging role, there has been a large number of studies on the effect of rapamycin and mTOR signaling on various aspects of the immune system, and there have been several recent review articles in this area [88][89][90][91].…”
Section: Effect Of Rapamycin On the Immune Response To Infectious Agementioning
confidence: 99%
“…The mammalian target of rapamycin (mTOR) is a serine-threonine kinase which belongs to the phosphatidylinositol-3 kinases (PI3K) family that senses and inte-grates environmental and intracellular signals to direct cellular response. 133,134 Activation of mTOR can drive cellular aging, and inhibition of mTOR by rapamycin has been shown to delay aging and induce autophagy in experimental models and has the potential for translation for age-associated diseases such as cancer. 134 In the murine model, mTOR activity is increased in aged HSCs compared to young.…”
Section: Rapamycinmentioning
confidence: 99%
“…In addition, many currently discussed small molecule strategies are hampered by inadequate biodistribution (rapamycin, curcumin) 133,159 and toxicity from interactions with off-target cells (metformin). 178 The marriage of these interventions alongside novel drug delivery vehicles may potentially increase efficacy alongside decreasing toxicity by ensuring the drug is delivered to only the target cell of interest (Figure 3).…”
Section: Future Workmentioning
confidence: 99%